Dampak Media Sosial Terhadap Akhlak Di Era Globalisasi - Zaky Raihan; Dinda Putri Hasanah; Wardah Yuni Kartika; Lidyazanti Lidyazanti; Wismanto Wismanto (Jurnal Budi Pekerti Agama Islam, 2024)
Social media is an online media with it' s social media users can easily to share, create social networks, forums and virtual worlds that can be received quickly in the community. In the era of globalization this social media benefit in society as a medium of social media entertainment is one of the most common media players by the community because through the media the community can to develop creativity in various social networks quickly and efficient. The purpose of this study is to know the impact of social media to the character of its users in the era of globalization or the modern decomage from Al-Qur’an perspective. This research uses qualitative research method with literature approach or library research, data collection by looking for sources and merrking from various sources such as books, journals, articles and existing research. The results showed that social media are media that often worked by the community in all circles, social media has a positive or negative effect for its users and otherwise social media can affect morals from someone